2010
DOI: 10.1038/ejcn.2010.94
|View full text |Cite
|
Sign up to set email alerts
|

Whole grain in children's diet: intake, food sources and trends

Abstract: Objective: To quantify the intake of grain and whole grain, and their food sources, as well as to investigate the age and time trends over the last decade in a sample of German children and adolescents. Methods: Dietary records from the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) Study were used for conducting this work. A total of 5067 3-day weighed dietary records of 821 2-to 18-year-old children and adolescents collected between 1997 and 2008 were analysed using linear mixed-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 25 publications
1
26
1
2
Order By: Relevance
“…It was shown, using dietary surveys, that in most cases the intake of whole-grain is too low in adults (Cleveland et al 2000, Thane et al 2005) as well as in children and adolescents (Brady et al 2000). Alexy et al (2010) also reported a negative age trend of whole-grain intake. Therefore, it is important to prevent the risk that girls, aiming to reduce their weight, turn to self-made diets lacking in carbohydrates.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It was shown, using dietary surveys, that in most cases the intake of whole-grain is too low in adults (Cleveland et al 2000, Thane et al 2005) as well as in children and adolescents (Brady et al 2000). Alexy et al (2010) also reported a negative age trend of whole-grain intake. Therefore, it is important to prevent the risk that girls, aiming to reduce their weight, turn to self-made diets lacking in carbohydrates.…”
Section: Resultsmentioning
confidence: 95%
“…Similarly to a previous study (Toselli et al 2010), we observed a higher proportion of underweight subjects among girls (especially adolescents) than among boys, as well as a lower proportion of obese and overweight. Several authors (Marlett et al 2002, Kaline et al 2007, Mellen et al 2008, Alexy et al 2010) have reported the health effects of whole grains with respect to heart disease, cancer, gastrointestinal health, diabetes, and weight management studies. Despite in most cases these health effects have only been shown for adults, an elevated whole-grain intake may be desirable already in early life, as dietary habits develop during the early childhood and can track until adulthood (Lake et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, our results indicate that whole grain intakes are much below the reported intakes in other populations. Studies in the USA [29, 46], UK [21], Germany [25], Ireland [26, 27], Denmark, Norway and Sweden [24] reported a daily consumption of more than 13 g/day in children/adolescents (range 13–54 g/day) and 20 g/day in adults/older adults (range 20–51 g/day). Only in France [19] the whole grain intakes were comparable to those found in Italy (5 g/day in adults/older adults and 4 g/day in children/adolescents).…”
Section: Discussionmentioning
confidence: 99%
“…WG intake in children varies by country depending on the food culture and is lower in English-speaking countries such as United Kingdom, United States, and Ireland (9-19 g) (7)(8)(9) and higher in north European countries such as Germany and Denmark (20-58 g/d) (10,11) where children eat WG rye bread as a staple food and in Denmark especially for lunch (12).…”
Section: Introductionmentioning
confidence: 99%
“…The HLMs and snacks included some WG products among other food items (8,9). Dietary intake during the school meal study was measured by a self-administered and intuitive Web-based Dietary Assessment Software for Children (WebDASC) that was developed for the purpose (10).…”
Section: Introductionmentioning
confidence: 99%